Exploring Systemic Influences on Data-Informed Learning: Document Review of Policies, Procedures, and Legislation from Canada and the United States. Issue 3 (17th May 2022) - Wiljer, David; Williams, Spencer; Charow, Rebecca; Campbell, Craig; Davis, Dave; Younus, Sarah; Mylopoulos, Maria; Okrainec, Allan; Silver, Ivan; Tavares, Walter; Sockalingam, Sanjeev
Abstract : Introduction: Despite the support for and benefits of data-driven learning, physician engagement is variable. This study explores systemic influences of physician use of data for performance improvement in continuing professional development (CPD) by analyzing and interpreting data sources from organizational and institutional documents. Methods: The document analysis is the third phase of a mixed-methods explanatory sequential study examining cultural factors that influence data-informed learning. A gray literature search was conducted for organizations both in Canada and the United States. The analysis contains nonparticipant observations from professional learning bodies and medical specialty organizations with established roles within the CPD community known to lead and influence change in CPD. Results: Sixty-two documents were collected from 20 Canadian and American organizations. The content analysis identified the following: (1) a need to advocate for data-informed self-assessment and team-based learning strategies; (2) privacy and confidentiality concerns intersect at the point of patient data collection and physician-generated outcomes and need to be acknowledged; (3) a nuanced data strategy approach for each medical specialty is needed. Discussion: This analysis broadens our understanding of system-level factors that influence the extent to which health information custodians and physicians are motivated to engage with data for learning.